Teaching competency testing among Malaysian school teachers - Hamdan, Abdul Rahim (EuroJournals, Inc., 2010)
A major goals of this research, is to study the teaching competency and dominant characteristics 309 teachers from different secondary / primary schools in Johor Bahru. Their competencies are determined through teaching skills, concern for school, concern for students and concern for self, forming a comprehensive and practical model of teachers’ competency characteristics. The result shows that all teachers are competent, and there are significant relationships between teaching competency and gender, specializations, and academic achievement. It is suggested that teachers have to enhance his or her competent in other elements such as subject knowledge, teaching prowess, classroom management, instructional planning, collegiality, concern on schools, concern on students and concern on self to build the image and ability as a competent teacher.